JANE EYRE: VOLUME 2 [AUDIO LIVRO/CD] - BRONTE, CHARLOTTE, 1816-1885; BELL, FLORENCE; RICHARDSON, JAMES (LONDON MACMILLAN PUBLISHERS LIMITED, 2005)
FROM THE TIME SHE WAS ORPHANED, JANE KNOWS NOTHING BUT UNKINDNESS. SHE MUST HER WAY IN A WORLD THAT IS OFTEN CRUEL AND INDIFFERENT. WHEN IT LOOKS AS IF JANE IS GOING TO BE HAPPY AT LAST, FATE DEALS HER ITS HARSHEST BLOW. BUT JANE HAS SPIRIT, STRENGHT, AND DETERMINATION. NOW SHE MUST USE THEM ALL TO WIN LOVE AND TRUE HAPPINESS.
INGLÊS
PARTE INTEGRANTE DO LIVRO "JANE EYRE" DE CHARLOTTE BRONTE ADAPTADO POR FLORENCE BELL.
Keywords: CRIANCAS; LITERATURA INFANTOJUVENIL; LITERATURA; FICCAO; JOVENS; CRIANCAS ABANDONADAS; CONFLITOS; SECULO XIX; DRAMA; ROMANCES; DETERMINACAO; LITERATURA INGLESA; ORFAOS; ROMANCE INGLES; GOVERNANTAS; ROMANCE; ORFANATOS; AUDIOLIVRO